Desain dan Uji Coba Lembar Kerja Peserta Didik (LKPD) Berbasis Probing-Prompting pada Materi Sistem Periodik Unsur - Rini Karsini Rohman; Pangoloan Soleman Ritonga (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
This research is motivated by students' chemical mastery in learning is still low, especially for abstract concept/theory material. This can be seen from students being less active and lacking memory in following the learning process. In addition, schools only rely on textbooks that make students less interested in learning and there is no student workbook to support students' understanding. This research aimed at knowing the appropriateness of the instructional media design in the form of Probing-Prompting based student workbook on Periodic System of the Elements lesson. It was administered at State Islamic Senior High School 1 Pekanbaru. It was R&D (Research and Development) with 4-D model, and it was limited to 3 models—define, design, and development. The subjects of this research were the experts of material, the experts of media, and the experts of language, Chemistry subject teachers, 10 students at the tenth grade of MIA 1. The object was Probing-Prompting based student workbook on Periodic System of the Elements lesson. The research findings showed that Probing-Prompting based student workbook was appropriate to be used and it was based on the results of validity and practicality levels. The percentage of validity level obtained was 85.78% (very valid) and the practicality level was 85.33% (very practical). Based on theses results, it could be identified that Probing-Prompting based student workbook could be tested further. KeywordsStudent Workbook, Probing-Prompting, Periodic System of the Element